A comprehensive review on modular multilevel converters, submodule topologies, and modulation techniques - Barros, Luis A. M. (2022)
The concept of the modular multilevel converter (MLC) has been raising interest in research in order to improve their performance and applicability. The potential of an MLC is enormous, with a great focus on medium- and high-voltage applications, such as solar photovoltaic and wind farms, electrified railway systems, or power distribution systems. This concept makes it possible to overcome the limitation of the semiconductors blocking voltages, presenting advantageous characteristics. However, the complexity of implementation and control presents added challenges. Thus, this paper aims to contribute with a critical and comparative analysis of the state-of-the-art aspects of this concept in order to maximize its potential. In this paper, different power electronics converter topologies that can be integrated into the MLC concept are presented, highlighting the advantages and disadvantages of each topology. Nevertheless, different modulation techniques used in an MLC are also presented and analyzed. Computational simulations of all the modulation techniques under analysis were developed, based on four cascaded full-bridge topologies. Considering the simulation results, a comparative analysis was possible to make regarding the symmetry of the synthesized waveforms, the harmonic content, and the power distribution in each submodule constituting the MLC.